1997
DOI: 10.1557/jmr.1997.0203
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures of two-phase Ti–Cr alloys containing the TiCr2 Laves phase intermetallic

Abstract: Microstructures of two-phase Ti-Cr alloys (Ti-rich bcc 1 TiCr 2 and Cr-rich bcc 1 TiCr 2 ) are analyzed. A variety of TiCr 2 precipitate morphologies is encountered with different nominal alloy compositions and annealing temperatures. Lattice constants and crystal structures are determined by x-ray diffraction (XRD) and transmission electron microscopy (TEM). Orientation relationships between the beta bcc solid solution and C15 TiCr 2 Laves phase are understood in terms of geometrical packing, and are consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…The as-cast binary alloys were generally single-phase bcc �. Upon annealing, the different nominal compositions of the Ti-Cr alloys produced very different microstructures of (Ti,Cr)-bcc+ TiCr 2 and are described in detail else where [26]. The Ti-rich alloys contained discrete precip itates of the TiCr 2 Laves intermetallic (Fig.…”
Section: Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The as-cast binary alloys were generally single-phase bcc �. Upon annealing, the different nominal compositions of the Ti-Cr alloys produced very different microstructures of (Ti,Cr)-bcc+ TiCr 2 and are described in detail else where [26]. The Ti-rich alloys contained discrete precip itates of the TiCr 2 Laves intermetallic (Fig.…”
Section: Microstructuresmentioning
confidence: 99%
“…A range of interesting microstructures has been revealed with different Ti-Cr alloy composi tions and annealing treatments [26]. TiCr 2 in a large volume fraction of Ti-rich, bcc solid solutions and Cr-rich, bcc solid solutions are examined.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the Cr-rich phase confers oxidation resistance and toughness, whilst the Laves phase provides superior high temperature strength and creep performance. To date numerous studies have been reported on various binary Cr-X systems [8,9,11,12]. However, there have been few studies in which the effect of a ternary alloying addition has been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of phase could be estimated from the results of previous studies. [23][24][25] Figure 4 is the replot of previous reports and the lattice parameter can be expressed as Lattice parameter (nm) ¼ 0:3310875 À 0:04354 X Cr Accordingly, the lattice parameter of phase in this study corresponds to the Cr content of about 13 at%. This is about half of the average Cr composition of the starting wire.…”
Section: Resultsmentioning
confidence: 81%